Wertigkeit der Hoden Perfusionsszintigraphie - Kotzerke, J.; Erpenbach, K.; Hengst, W. (Nuklearmedizin - NuclearMedicine, 1987)
Perfusion scintigraphy of the testicles has still its place, in addition to scrotal ultrasound imaging, in the investigation of the “acute scrotum”. It reveals scintigraphic patterns typical for twisted testicle and acute or subacute epididymitis. Especially in the Bundeswehr, with its large number of young men, this method enhances the diagnostic spectrum and helps in making surgical decisions. However, in the examination of scrotal masses, ultrasound imaging or surgery is to be preferred.